Problems in using the U.P. Diliman Main Library as perceived by foreign students - Chumnong Wongchachom (1988)
The problems in using the U.P. Diliman Main Library (UPDML) as perceived by foreign students enrolled in the University of the Philippines Diliman in the second semester, AY 1987-1988 is the subject of this study. Specifically, the study aims to identify the problems which they perceived in the use of the library resources and services of UPDML to determine specific reader's advisory assistance which the foreign students need in the UPDML, and to find out if the problems they encounter in their studies affect their use of UPDML.